Emerging voices in ICT and agriculture: Shaping the future of ACP rural development using ICTs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2012)
Following an essay competition (‘Youth finding solutions to challenges in agriculture and rural development using ICTs!’) initiated by the ARDYIS project, this inspiring synthesis is based on 18 of the best essays. Topics include how ICTs can be used to address challenges and improve access to markets in agriculture, plus examples of young producers who have used ICTs successfully in their work.